2017
DOI: 10.1001/jamaoncol.2016.6905
|View full text |Cite
|
Sign up to set email alerts
|

Using the National Cancer Database for Outcomes Research

Abstract: The NCDB offers a critically important perspective on cancer care in the United States. To capitalize on its strengths and adjust for its limitations, investigators and their audiences should familiarize themselves with the advantages and shortcomings of the NCDB, as well as its evolution over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
649
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 865 publications
(681 citation statements)
references
References 35 publications
2
649
0
1
Order By: Relevance
“…33,34 Multiple studies have shown that right-and left-sided cancers differ markedly in underlying biologic drivers. Further limitations of the NCDB are well summarized by Boffa et al 38 Although the implications of these epidemiologic data support changes in screening guidelines, large prospective screening studies of patients younger than 50 years are strongly needed to determine which younger patients are most at risk for CRC and to better determine the risks, benefits, and costs of screening this population. [35][36][37] Because of the differences in biology, the etiology of the rising prevalence in younger adults may differ in right and left colon cancers.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Multiple studies have shown that right-and left-sided cancers differ markedly in underlying biologic drivers. Further limitations of the NCDB are well summarized by Boffa et al 38 Although the implications of these epidemiologic data support changes in screening guidelines, large prospective screening studies of patients younger than 50 years are strongly needed to determine which younger patients are most at risk for CRC and to better determine the risks, benefits, and costs of screening this population. [35][36][37] Because of the differences in biology, the etiology of the rising prevalence in younger adults may differ in right and left colon cancers.…”
Section: Resultsmentioning
confidence: 99%
“…A very abbreviated and less granular comorbidity scoring systems called Klabunde et al [20] or Deyo et al [21] adaptations of the originally validated Charlson comorbidity index [13] are included as a variable in some national databases such as National Cancer Database [22] or SEER-Medicare linked data sets to study outcomes [23]. In using these abbreviated tools, subjects are assigned a score of only 0, 1, or ≥2 in contrast to the original validated score used in the current study that can reach up to 25 points [13].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Patients with sarcomatoid HCC were identified from the NCDB Participant Use Data File using the combination of International Classification of Diseases for Oncology, 3rd Edition (ICD-O-3) topography code C22.0 (liver), histology code 8173, and behavior code 3 (malignant tumor). 14 As previously reported, the NCDB is a database collected and updated by the American College of Surgeons Commission on Cancer (CoC) and the American Cancer Society.…”
Section: Patients and Data Sourcementioning
confidence: 99%